Pengaruh Efikasi Diri dan Partisipasi dalam Organisasi Mahasiswa Terhadap Prestasi Mahasiswa S1 Manajemen FEB UNEJ - Ahmad Safi’I (Fakultas Ekonomi dan Bisnis, 2026)
This study responds to high academic performance standards at FEB UNEJ by examining how student achievement (Y) is influenced by internal factors like self-efficacy (X₁) and external factors like participation in student organizations (X2). Methods: This quantitative explanatory research sampled 139 active Management students (cohorts 2022-2024) who serve as organization administrators, selected via the Slovin formula and proportionate random sampling. Data were collected through questionnaires, interviews, and observations, and analyzed using Multiple Linear Regression in SPSS. Results: The regression analysis demonstrates that self-efficacy partially has a positive and significant effect on achievement (tcount 4,942 > ttable 1,977, sig. 0.000). Conversely, organization participation does not partially affect achievement significantly (tcount 1,976 < trabie 1,977, sig. 0.050). Simultaneously, both variables significantly impact achievement (Fcount 24,503 > Ftable 3,062, sig. 0.000). Analysis: The Adjusted R Square model reveals a coefficient of 0.254, which indicates that self-efficacy and organization participation collectively account for 25.4% of the variance in student achievement, while the remaining 74.6% is explained by external factors outside this research model. Discussion: High self-efficacy acts as a driving force that helps students view academic burdens as challenges. However, organization involvement fails to increase achievement linearly because heavy operational and execution-level tasks often trigger role conflicts and reduce study time. Students are advised to improve time management, and future researchers should explore additional variables.
:: Finalisasi file repositori 5 Agustus 2026_Kurnadi
Keywords: Self-Efficacy; Student Organization Participation; Student Achievement.